Structure and gating of kainate receptors - Gangwar, Shanti P.; Yelshanskaya, Maria V.; Yen, Laura Y.; Newton, Thomas P.; Sobolevsky, Alexander I. (Frontiers in Pharmacology, 2025)
Ionotropic glutamate receptors (iGluRs) are crucial for fast excitatory neurotransmission in the mammalian central nervous system (CNS). Kainate receptors (KARs), a subclass of iGluRs, are tetrameric, ligand-gated ion channels that play key modulatory roles at both pre- and post-synaptic sites within neuronal circuits and in the regulation of synaptic plasticity. KARs are composed of GluK1-GluK5 subunits, with subunits GluK1-GluK3 forming functional homo- and heteromeric channels, while GluK4-GluK5 assemble as obligate heteromers, partnering with subunits GluK1-GluK3. Over the past two decades, numerous homomeric and heteromeric structures of isolated domains and the full-length receptor have been solved in various functional states, providing detailed descriptions of functional mechanisms, thereby addressing several longstanding questions in the field of KAR biology. These studies revealed overall structural similarity of KARs with other iGluRs, particularly AMPA receptors in the closed and activated states, and the agonist-bound non-conducting state adopting a conformation which is different from other iGluRs. This review highlights recent structural insights into gating and pharmacological regulation of KARs, offering deeper understanding of their roles in synaptic transmission and neuronal signaling.